The evolution of ideas about the gene - Горенська, О. В.; Тагліна, О. В.; Воробйова, Л. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The idea about the gene reflects the level of development of modern genetics. The classical concept about the gene as a unit of mutation, recombination and function, proposed by T.Morgan in 1926, has undergone remarkable changes. The divisibility of the gene, intragene crossing over, overlapping genes which discovered have shown diversity and complexity of gene networks. In the review the basic stages of formation of knowledge about genes as material carriers of the hereditary information have been considered. The analysis of collected modern information about the gene structure, function and about features of the gene activity regulation has been performed.